Position Control of Linear Switched Reluctance Machine using Flower Pollination Algorithm - Nunes, H.G.G. (2020)
This paper presents a control mechanism for position control of linear switched reluctance machine (LSRM) using flower pollination algorithm (FPA). The control mechanism consists of the proportional-integral-derivative (PID) position controller. Therefore, the problem of determining the optimal values for the gains (proportional, integral and derivative) of the position controller is defined as an optimization problem that aims to obtain the optimal gains by minimizing the integral of time multiplied by absolute error (ITAE) of the position. In order to evaluate the performance of the FPA different operating scenarios were considered and the salp swarm algorithm (SSA) and multi-verse optimizer (MVO) were also implemented for results comparison. The results reveal that position control based on the optimal gains obtained by the FPA provides the smallest error, improving the dynamic performance of the LSRM